(untitled) (African Journal of Biomedical Research, 2023)
Due to the increasing resistance of the superbug, Staphylococcus aureus, and many other pathogenic microorganisms to conventional antibiotics, there is a need to search for new and better antimicrobial substances. This study was carried out to evaluate the antimicrobial efficacy of the African walnut plant, Plukenetia conophora against antibiotic-resistant Staphylococcus aureus. 350 wound swab samples were obtained. Isolation, characterization, identification and antibiotic susceptibility testing of Staphylococcus aureus isolates were done using standard microbiological procedures. Antimicrobial activity screening of the different extracts on the antibiotic-resistant isolates was performed with the agar well diffusion technique. Varying concentrations (100mg/ml, 50mg/ml, 25mg/ml,12.5mg/ml) of both the aqueous and ethanol extracts of the leaves of the plant were assayed for antimicrobial potential and their antimicrobial activity was compared with the antibiotic, Nitrofurantoin 300µg (NIT) for each of the antibiotic-resistant Staphylococcus aureus isolates. Only the leaf extracts possessed antimicrobial potential against antibiotic-resistant Staphylococcus aureus. Also, ethanol extracts of the leaves displayed the higher antimicrobial potential of the leaf extracts is dose-dependent and is higher than that of NIT upon comparison. The MIC and the MBC were found to be 25mg/ml and 100 mg/ml respectively for both ethanol and aqueous leaf extracts. Flavonoids, alkaloids, tannins, and phenols were observed to be responsible for the antimicrobial potential of the leaves of Plukenetia conophora. This study reveals that the leaves of Plukenetia conophora possess antimicrobial property and as such can be used as an alternative to conventional antibiotics for the treatment of infections caused by multidrug-resistant Staphylococcus aureus.